2013
DOI: 10.3109/19396368.2013.862316
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial receptivity markers in infertile women stimulated with letrozole compared with clomiphene citrate and natural cycles

Abstract: Though various advantages associated with the use of letrozole as an ovulation inducing drug are documented, there is inadequate information regarding its effect on endometrial receptivity. Expression of endometrial receptivity markers including a v b 3 integrin, L-selectin, LIF, and pinopods during the implantation window in infertile women stimulated with letrozole or clomiphene citrate (CC), and spontaneous cycles is investigated. A total of 36 women were included in the study out of which 16 women were dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…In this way, Miller et al concluded that the lack of endometrial αvβ3 integrin expression is associated with a poor prognosis outcome in IVF cycles that might be improved with letrozole co-treatment [22]. Elsewhere, Ganesh et al, in a preliminary study reported that OS with the use of letrozole was associated with a significant increase in the epithelial and stromal expression of uterine receptivity markers, including integrin, leukaemia inhibitory factor, and L-selectin, in women with unexplained infertility compared with natural cycles [23]; all of which may have positive effects on the pregnancy rate after ET [2]. Meanwhile, we observed a slight increase in the endometrial thickness on the day of ET in the letrozoletreated group.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, Miller et al concluded that the lack of endometrial αvβ3 integrin expression is associated with a poor prognosis outcome in IVF cycles that might be improved with letrozole co-treatment [22]. Elsewhere, Ganesh et al, in a preliminary study reported that OS with the use of letrozole was associated with a significant increase in the epithelial and stromal expression of uterine receptivity markers, including integrin, leukaemia inhibitory factor, and L-selectin, in women with unexplained infertility compared with natural cycles [23]; all of which may have positive effects on the pregnancy rate after ET [2]. Meanwhile, we observed a slight increase in the endometrial thickness on the day of ET in the letrozoletreated group.…”
Section: Discussionmentioning
confidence: 99%
“…Cortinez et al observed similar EMT rates and endometrial morphology in a group receiving letrozole treatment compared to NC [13]. Furthermore, Ganesh et al reported that letrozole induces higher expression of integrin in the endometrial epithelium than NC, which improves the endometrial environment [14]. The superiority of letrozole could also be due to activation of the Wnt/B-catenin pathway [36,37].…”
Section: Discussionmentioning
confidence: 98%
“…Numerous researchers have investigated the characteristics of letrozole for induction of ovulation. Letrozole has been proved to promote the endometrial thickness required for embryo implantation and does not impair endometrial receptivity [13,14]. Moreover, unlike CC, it has no anti-oestrogenic effects on the endometrium and cervical mucus [15].…”
Section: Introductionmentioning
confidence: 99%
“…Letrozole improves the outcome of FET probably by increasing the expression of receptivity marker, integrin, among ART patients with low integrin expression. Ganesh et al demonstrated that the use of letrozole is associated with significantly increased expression of integrin in the uterine endometrium, compared with natural cycles in patients with unexplained infertility 17. Furthermore, Miller et al also reported that letrozole upregulates the expression levels of integrin and significantly increases the pregnancy and implantation rates after IVF among women who lacked normal expression levels of integrin 18.…”
Section: Discussionmentioning
confidence: 99%